Limited ability of DNA polymerase kappa to suppress benzo[a]pyrene‐induced genotoxicity in vivo. (27th October 2017) - Masumura, Kenichi; Toyoda‐Hokaiwado, Naomi; Niimi, Naoko; Grúz, Petr; Wada, Naoko A.; Takeiri, Akira; Jishage, Kou‐ichi; Mishima, Masayuki; Nohmi, Takehiko
Abstract : DNA polymerase kappa (Polk) is a specialized DNA polymerase involved in translesion DNA synthesis. To understand the protective roles against genotoxins in vivo, we established inactivated Polk knock‐in gpt delta (inactivated Polk KI) mice that possessed reporter genes for mutations and expressed inactive Polk. In this study, we examined genotoxicity of benzo[ a ]pyrene (BP) to determine whether Polk actually suppressed BP‐induced genotoxicity as predicted by biochemistry and in vitro cell culture studies. Seven‐week‐old inactivated Polk KI and wild‐type (WT) mice were treated with BP at doses of 5, 15, or 50 mg/(kg·day) for three consecutive days by intragastric gavage, and mutations in the colon and micronucleus formation in the peripheral blood were examined. Surprisingly, no differences were observed in the frequencies of mutations and micronucleus formation at 5 or 50 mg/kg doses. Inactivated Polk KI mice exhibited approximately two times higher gpt mutant frequency than did WT mice only at the 15 mg/kg dose. The frequency of micronucleus formation was slightly higher in inactivated Polk KI than in WT mice at the same dose, but it was statistically insignificant. The results suggest that Polk has a limited ability to suppress BP‐induced genotoxicity in the colon and bone marrow and also that the roles of specialized DNA polymerases in mutagenesis and carcinogenesis should be examined not only by in vitro assays but also by in vivo mouse studies. We also report the spontaneous mutagenesis in inactivated Polk KI mice at young and old ages. Environ. Mol. Mutagen. 58:644–653, 2017. © 2017 Wiley Periodicals, Inc.